2021
DOI: 10.1152/ajpgi.00425.2020
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal organoids: roadmap to the clinic

Abstract: Recent advances in intestinal organoid research, along with encouraging preclinical proof-of-concept studies, have revealed significant therapeutic potential for induced pluripotent stem cell (iPSC) derived organoids in the healing and replacement of severely injured or diseased bowel [1-3]. To fully realize the tremendous promise of stem cell organoid-based therapies, careful planning aligned with significant resources and efforts must be devoted demonstrating their safety and efficacy to meet critical regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Our study provides a snapshot of the chronic hyperlipidemia effect on intestinal cell differentiation by using small intestinal organoid platforms. Organoids allow for the investigation of how biologically active intestinal cells interact in the gut, how TFs regulating gut cell differentiation interact with each other, and how nutritional changes causing metabolic diseases could impair these aspects [ 16 , 28 , 29 ]. In addition, our 3D platform could represent a starting point for the development of on-chip model in order to obtain an enhancement of the understanding of physiopathological alterations that could lead to an improvement in the prevention and treatment of complex chronic diseases such as obesity and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides a snapshot of the chronic hyperlipidemia effect on intestinal cell differentiation by using small intestinal organoid platforms. Organoids allow for the investigation of how biologically active intestinal cells interact in the gut, how TFs regulating gut cell differentiation interact with each other, and how nutritional changes causing metabolic diseases could impair these aspects [ 16 , 28 , 29 ]. In addition, our 3D platform could represent a starting point for the development of on-chip model in order to obtain an enhancement of the understanding of physiopathological alterations that could lead to an improvement in the prevention and treatment of complex chronic diseases such as obesity and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…One major hurdle with this approach lies in identifying a delivery method that supports cell survival, engraftment, and retention at the site of administration. [49] A proof-of-concept study demonstrating that organoids engraft into injured tissue was reported by Yui et al [5] They transplanted LGR5+ mouse colonic organoids to the colon in a DSS-induced colitis murine model. To test the regenerative capacity of the intestinal organoids, they prepared a single cell suspension with ≈500 organoids and delivered these via an intracolonic infusion.…”
Section: In Vivo Delivery Of Intestinal Organoids To Injury Modelsmentioning
confidence: 97%
“…When considered for in vivo intestinal regenerative therapy and clinical translation, both iPSC‐ and ASC‐derived are promising candidates, however, manufacturing practices, time and costs, autologous versus allogeneic tissue source, and availability of tissues should be considered. [ 49 ]…”
Section: Human Intestinal Organoid Culture and Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, the generation of intestinal organoids has provided a rich reference for understanding intestinal pathology. 97 99 Organoid models can effectively mimic the state of intestinal diseases, including motility disorders, malabsorptive diarrhea, inflammation, infection, and cancer. 40 , 75 , 95 , 100 Microvillus inclusion disease (MVID) is a congenital disease of the intestinal epithelium that causes malnutrition and is characterized by diffuse villus atrophy or absence of apical microvilli.…”
Section: The Application Of Organoidsmentioning
confidence: 99%